The Effect of Quantum Learning Method Toward Students Vocabulary Mastery in Grade V of SDN 03 Pakan Labuah - Agustia, Sri Novelta; Safitri, Loli; Melani, Melyann; Syahrul, Syahrul (Continuous Education: Journal of Science and Research, 2025)
This study explores the effect of the Quantum Learning method on vocabulary mastery among fifth-grade students at SDN 03 Pakan Labuah. The research used a quasi-experimental design, where an experimental group taught using Quantum Learning and a control group receiving traditional teaching methods. Data were collected through pre-tests and post-tests measuring students' vocabulary mastery. The results demonstrated a significant improvement in the experimental group's vocabulary scores (p-value = 0.000), suggesting that the Quantum Learning method had a positive impact on vocabulary acquisition. However, no significant difference was found between the experimental and control groups when comparing overall vocabulary mastery scores (p-value = 0.242). Despite this, the experimental group outperformed the control group in post-test results, further supporting the effectiveness of the Quantum Learning method in enhancing vocabulary mastery. This study contributes to the growing body of research on innovative teaching methodologies, offering valuable insights into the application of Quantum Learning in language education. Future research should focus on exploring long-term effects and the role of contextual factors in the method's effectiveness.